Translation movements in the modernization processes of Turkey and China - Bayraktar-Özer, Özge (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
The migration of knowledge between cultures is ubiquitous, whether it happens naturally on encountering communities or is consciously planned by authorities to learn from one another. As nations constantly share their scientific and philosophical knowledge with others, translation takes on a key role in the transmission of not only knowledge, but also the advancement of all aspects of the source culture. In this respect, the Qing and Ottoman empires, after experiencing military defeats, were able to recognise the progress made by certain nations as a result of the Industrial Revolution. The knowledge transfer from these industrialized countries therefore became part of the attempts by states, private institutions and reformers to catch up with these countries in the area of development through increased translation initiatives. Trends such as these subsequently continued to shape the culture-planning processes in many countries. Against this background, the present study aims to shine a light on the parallel course of translation movements in the modernization processes of China and Turkey from the mid-19th to the mid-20th century. It offers an overview of the translation movements crafted in an analogous pattern that entailed three stages of implementing translation activities in the modernization efforts of the two countries.